Research on Optimization Path of TEM-4 Writing Based on Scoring Criteria - Chen, Xiuhong; Fu, Tingyi (Journal of Educational Research and Policies, 2025)
As a core indicator for measuring students’ writing ability in the basic stage of English majors, the scoring criteria of TEM-4 writing plays a direct guiding role in English teaching practice and examination preparation strategies. Therefore, based on the theoretical framework of scoring criteria of TEM-4 writing, this paper systematically analyzes the common problems existing in current students’ writing (such as insufficient relevance of content, loose logical structure, and non-standard language expression), and proposes an optimized path for TEM-4 writing from the core dimensions of scoring criteria (content, organization, and language). The research aims to provide practical and optimized strategies for English writing teaching practice, helping students accurately meet the scoring requirements and improve their writing skills and test performance.